(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2026)
Low fat content weakens gel structure and sensory acceptance, milk cream addition improves yogurt quality. This study aims to analyze the effect of adding cream on the characteristics of yogurt made from reconstituted skim milk powder. The treatment consisted of five cream concentrations (0%, 3%, 4%, 5%, and 6%) using a completely randomized design (CRD) with three replicates. The parameters observed included physicochemical properties (pH, aw, viscosity, total acid titratable, syneresis, moisture content, and ash content), organoleptic properties (hedonic test and scale), microbiological properties (total lactic acid bacteria and total plate count), and microstructure using polarized and non-polarized light microscopes. The result showed that all treatments met the yogurt quality standards based on SNI 2981:2009. The addition of milk cream had a significant effect on the physical, chemical, organoleptic, and microstructure characteristics, but had no effect on color and total microbes. Increasing the milk cream concentration produced yogurt with a thicker texture, milder taste, and aroma that was more preferred by the panelists. Microscopically, the distribution of fat globules was more even and the protein-fat interaction was more integrated in the gel matrix, enhancing viscosity and reducing syneresis.